Mast Cell Leukaemia: c-KIT Mutations Are Not Always Positive - Magalie Joris; Sophie Georgin-Lavialle; Marie-Olivia Chandesris; Ludovic Lhermitte; Jean-François Claisse; Danielle Canioni; Katia Hanssens; Gandhi Damaj; Olivier Hermine; Mohammed Hamidou (Case Reports in Hematology)
Mast cell leukemia (MCL) is a rare and aggressive disease with poor prognosis and short survival time. D816V c-KIT mutation is the most frequent molecular abnormality and plays a crucial role in the pathogenesis and development of the disease. Thus, comprehensive diagnostic investigations and molecular studies should be carefully carried out to facilitate the therapeutic choice. A MCL patient’s case with rare phenotypic and genotypic characteristics is described with review of major clinical biological and therapeutic approaches in MCL.